Sifat Fisis dan Keawetan Alami Kayu Pengkih Terhadap Serangan Rayap Tanah (Macrotermes Gilvus) - Jon Herianta Ginting; yunus afifuddin; Luthfi Hakim (Program studi Kehutanan USU, 2012)
Availability of wood species from natural forest that commonly used for building contructions, meuble, craft and industrial materials nowadays is increasingly limited and not balanced with increasing the needs of wood. To fulfill the needs should be used the species of wood that easily obtained, such as the species that are less well known from natural forest or cultivated by people. The purpose of this research is to evaluate the physical propersties and natural durability of pengkih wood towards termite attack. These physical properties testing is based on the ASTM D 143-94 standard with three replications in each sample. These natural durability of wood testing based on the SNI 01-7207-2006 standard with four replications in each sample. Based on the results of this research pengkih wood is including class II of wood strength, that have value of density substance is 1.5 and including class I of grade durability with percentage of weight lose about 0.3-0.6%. The smallest value of attack intensity is in the wooden base and the largest is in the end of the wood. . Key words : Pengkih Wood, physical properties, natural durability, termites